Intelligent Water Drop Based Coverage-Connectivity and Lifespan Maximization Protocol for Wireless Sensor Networks - Sharma, R.; Lobiyal, D.K. (Recent Patents on Engineering, 2019)
Background: A significant issue of consideration in wireless sensor networks is to reduce the energy utilization while preserving the required coverage and connectivity of an area of interest. We have revised all patents relating to preserving of energy in sensor motes of the wireless sensor networks. Methods: We proposed a novel; Intelligent Water Drop based coverage-connectivity and lifespan protocol which minimizes energy consumption of the network. In this routing protocol, sensors are partitioned into the connected first layer and connected successive layer sets and a scheduling mechanism has been used to activate and deactivate sensors. Multi-hoping is used to transmit packets from sensors to the Base Station and sensor with maximum residual energy has been selected as the next hop. Power wastage has been avoided by removing duplicate information through a common relay node. Results: We have derived the expected number of sensors required to cover an area of interest and our protocol gives a long life to the network. A theorem has been provided to validate the results for different communication ranges of sensors. Conclusion: The protocol has been compared with other protocols and it proved better than other protocols in terms of the lifespan and the coverage ratio of the area. Results approve that our protocol reduces the problem of energy holes and maintains the connectivity of the network.
Keywords: communication range